TORSIONAL BEHAVIOR OF RECTANGULAR BEAMS: A THEORETICAL AND LITERATURE-BASED REVIEW OF STRUCTURAL IMPLICATIONS - Kaur, Mandeep; Singh, Dr. Harvinder (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The torsional behavior of rectangular beams has been widely investigated in structural and mechanical engineering due to their practical relevance in buildings, bridges, and mechanical systems. This paper presents a theoretical overview of the torsional response of rectangular cross-section beams, emphasizing how variations in geometry affect stiffness, warping, and stress development. Drawing on established research, it explores classical and modern understandings of torsion in non-circular sections. A synthesis of past findings reveals consistent challenges in modeling warping and identifies optimal aspect ratios for efficient torsional resistance.